Clinical and genetic characteristics of 14 patients from 13 Japanese families with RPGR-associated retinal disorder: report of eight novel variants - Mawatari, Go (Hum Genome Var, 2019)
Variants in the retinitis pigmentosa GTPase regulator (RPGR) gene are a major cause of X-linked inherited retinal disorder (IRD). We herein describe the clinical and genetic features of 14 patients from 13 Japanese families harboring RPGR variants in a nationwide cohort. Comprehensive ophthalmological examinations were performed to classify the patients into one of the phenotype subgroups: retinitis pigmentosa (RP) and cone rod dystrophy (CORD). The mean age of onset/at examination was 13.8/38.1 years (range, 0–50/11–72), respectively. The mean visual acuity in the right/left eye was 0.43/0.43 (range, 0.1–1.7/−0.08–1.52) LogMAR unit. Eight patients had RP, and six had CORD. Whole-exome sequencing with target analyses identified 13 RPGR variants in 730 families with IRD, including 8 novel variants. An association between the phenotype subgroup and the position of variants (cutoff of amino acid 950) was revealed. To conclude, the clinical and genetic spectrum of RPGR-associated retinal disorder was first illustrated in a Japanese population, with a high proportion of novel variants. These results suggest the distinct genetic background of RPGR in the Japanese population, in which the genotype–phenotype association was affirmed. This evidence should be helpful monitoring and counseling patients and in selecting patients for future therapeutic trials.